Improved non‐invasive total haemoglobin measurements after in‐vivo adjustment. (7th May 2014) - Miyashita, R.; Hirata, N.; Sugino, S.; Mimura, M.; Yamakage, M.
Summary We hypothesised that an in‐vivo adjustment method and/or a newer sensor would increase the accuracy of non‐invasive and continuous haemoglobin monitoring (SpHb) measurements. Two sensors, the R1‐25 and R2‐25a (the newer version), were used with laboratory total haemoglobin concentration (tHb) values simultaneously recorded. In‐vivo adjusted SpHb (AdHb) was calculated by a simple formula: AdHb = SpHb − (1st SpHb − 1st tHb). The correlation coefficients between SpHb (or AdHb) and tHb were compared: SpHb in both sensors correlated strongly with tHb (p < 0.0001). In‐vivo adjustment improved the correlation coefficient between SpHb and tHb from 0.86 to 0.95 for the R1‐25 and from 0.83 to 0.93 for the R2‐25a. There was no difference between the R1‐25 and R2‐25a sensors. The in vivo adjustment method improved the accuracy of SpHb measurements in both sensors.